Correlation of MPV and IPF with Troponin-I Levels in Acute Coronary Syndrome Patients - Angelina, Marcellia; Permatasari, Ranti; Ganie, Ratna Akbari; Hasan , Refli (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Acute Coronary Syndrome (ACS) is a leading cause of death worldwide, with platelet activation playing a crucial role in the formation and evolution of atherothrombosis. Platelet indices, such as Mean Platelet Volume (MPV) and Immature Platelet Fraction (IPF), play a significant role as indicators of platelet activation. Troponin-I is a specific protein for the myocardium and serves as an ideal biomarker, providing crucial insights into the extent of myocardial damage. This study aims to identify the relationship between MPV and IPF with Troponin-I levels in patients with ACS. This research was a cross-sectional study involving 52 ACS patients undergoing treatment at H. Adam Malik Hospital, Medan, from February 2023 to May 2023. Blood samples were taken upon admission and examinations for MPV, IPF, and Troponin-I were conducted. The data were analyzed using SPSS software, and the Spearman test was employed. A p-value less than 0.05 was considered statistically significant. No correlation was found between MPV and Troponin-I, with a p-value of 0.251. Similarly, there was no correlation between IPF and Troponin-I, with a p-value of 0.090. However, a strong correlation was observed between MPV and IPF, with a p-value < 0.001 and an r-value of 0.840. The findings indicate insignificant results between MPV and IPF values in relation to Troponin-I levels in ACS patients.